The Swiss family Robinson - Warren, Eliza Gatewood; Wyss, Johann David, 1743-1818.; Pablo Marcos Studio (New York, N.Y. : Baronet Books, 1990)
'The Robinson family - shipwrecked on a desert island - must discover hidden strength in themselves to survive! Watch as they defend themselves against wild beasts, learn to hunt & fish, & to find shelter. As time passes, they grow to love the wild beauty of their island home, filled with rare animals, exotic bids & fragrant wild flowers. When a ship sails into their bay they must ask themselves if they really want to go home? This timeless story of inner resources & family love has thrilled & delighted young readers for over a hundred years!' --
Shipwrecked! -- Return to the wreck -- Nonsuch bridge -- House in the trees -- Tortoise takes us for a ride -- Journey into the interior -- Grizzle's strance companion -- Grotto that time forgot -- Holiday ... then horror! -- Terror at Felsenheim -- Mirage in the desert -- Capturing the world's biggest bird -- Cajack -- Mysterious message -- Sailor named Emily -- Sad farewell.
820.
'B224-11.
Translation of: Schweizerische Robinson.
820L
Keywords: Families -- Fiction; Families -- Juvenile Fiction; Survival after airplane accidents, shipwrecks, etc. -- Fiction; Survival after airplane accidents, shipwrecks, etc. -- Juvenile Fiction